Asia and Africa: International Economic and Political Trends - Alexei Dmitrievich Voskressenski; Sergei Ivanovich Lunev; Dmitrii Viktorovich Strel'tsov (Сравнительная политика)
Modern world is experiencing further geo-economic diversification of economic growth. The task of this section is to consider the implications of this process for political and economic development of Asia and Africa. What are the trends of socio-economic development in these countries? What are the key features of the relations between the North and the South nowadays? What role does modernization play in Asia and Africa? This section also analyzes the process of regionalization in the macro-region.